IRJA AND THE RISE OF THE MURJIA A STUDY BASED ON ISLAMIC SOURCES AND ORIENTALIST WRITINGS - Mohammed, Ali; Ismail, Farsat (Humanities Journal of University of Zakho, 2026)
Since its early inception, Islamic thought has witnessed extensive debate concerning the issues of faith (Iman) and, deeds (Amal) and their interrelation. One of the most prominent triggers of this debate was the emergence of the (Murjia) sect, which represented a direction contrary to that of the (Khawarij) and the (Shia) in its understanding of the concept of Iman and its stance toward the perpetrator of a major sin. Initially, (irja) was associated with a circumstantial political stance characterized by neutrality toward the civil strife (fitna) among the Companions, but it later evolved into an independent theological doctrine. This doctrine held that Iman is limited to internal belief and verbal declaration, without considering, Amal as part of its essence.This study examines the phenomenon of (irja) on three levels: the first is an internal analysis of the term through classical Islamic sources: the second concerns the emergence of the sect, as shown in Islamic sources, which indicate that the (Murjia) went through two distinct historical phases, the first political, and the second theological-doctrinal. The third level is the Orientalist perspective, in which views diverged regarding the roots of the (Murjia). Van Vloten (d. 1903) viewed Irjāʾ as a form of social protest that emerged as a result of the marginalization of certain Muslim groups. In contrast, Goldziher (d. 1921) considered it a peaceful social movement that arose in response to a political and religious crisis, rejecting takfīr (excommunication) and emphasizing inner faith despite outward sin. Meanwhile, Josef van Ess (d. 2021) argued that it originated in a political context after the fitna (civil strife) and later developed into a theological doctrine.The importance of this study lies in its presentation of a comparative analytical vision that integrates both Islamic sources and Orientalist studies, demonstrating that (irja) is not merely a theological issue but a complex intellectual, social, and political phenomenon that had a notable impact on the history of Islamic thought and contributed to shaping the contours of theological discourse in the early centuries.